The Effect Of Systemic Administration Of Zinc On The Gingival Crevicular Fluid Level Of Total Oxidant Capacity In Type 2 Diabetic Patients With Stage Ii And Iii Periodontitis After Non-Surgical Periodontal Therapy : A Randomized Clinical Trial - Abdulrahman Abdulqawi Awadh Abdulrab; Mona Darhous; Olfat Shaker; Weam Ahmed Elbattawy (Cairo : Abdulrahman Abdulqawi Awadh Abdulrab, 2021)
Aim: The aim of this study was to evaluate the effect of systemic administration of zinc on the total oxidant capacity in the gingival crevicular fluid level of controlled Type-2 diabetic patients with stage-II and III periodontitis after non-surgical periodontal therapy. Methodology: 28 controlled type 2 diabetic patients with periodontitis stages II or III were randomly assigned into two equal groups, test and control where both groups received non-surgical periodontal therapy while the test group received 50 mg zinc supplementation for 12 weeks. The level of total oxidant capacity (TOC) was measured in both groups in the GCF at baseline and after 3 months. HbA1c level, gingival index (GI), probing pocket depth (PPD) and clinical attachment level (CAL) were also reported at baseline and at 3 months postoperatively in both groups.Results: After 3 months a statistically significant decrease in mean omol/L TOC was reported in both groups while the test group showed statistically significantly lower mean omol/L TOC than the control group. No statistically significant difference in mean percentage HbA1c was reported after 3 months neither within each group nor between the two groups. In both groups there was a statistically significant decrease in median (range) GI scores, PPD reduction and mm CAL gain after three months with no statistically significant difference between both groups, while the test group showed statistically significantly lower median GI than the control group. Conclusions: scaling and root planning alone or in addition to Zinc could reduce the clinical periodontal parameters and the TOC in GCF in type 2 diabetic patients after 3 months but with no effect on the glycemic control and HbA1c levels
Thesis (M.Sc.) - Cairo University - Faculty of Oral and dental medicine - Department of periodontology
Issued also as CD
Keywords: zinc